Optimal Timing and Early Intervention With Anticoagulant Therapy for Sepsis-Induced Disseminated Intravascular Coagulation - Yamakawa, Kazuma (Clin Appl Thromb Hemost, 2019)
Optimizing diagnostic criteria to detect specific patients likely to benefit from anticoagulants is warranted. A cutoff of 5 points for the International Society on Thrombosis and Haemostasis overt disseminated intravascular coagulation (DIC) scoring system was determined in the original article, but its validity was not evaluated. This study aimed to explore the optimal cutoff points of DIC scoring systems and evaluate the effectiveness of early intervention with anticoagulants. We used a nationwide retrospective registry of consecutive adult patients with sepsis in Japan to develop simulated survival data, assuming anticoagulants were conducted strictly according to each cutoff point. Estimated treatment effects of anticoagulants for in-hospital mortality and risk of bleeding were calculated by logistic regression analysis with inverse probability of treatment weighting using propensity scoring. Of 2663 patients with sepsis, 1247 patients received anticoagulants and 1416 none. The simulation model showed no increase in estimated mortality between 0 and 3 cutoff points, whereas at ≥4 cutoff points, mortality increased linearly. The estimated bleeding tended to decrease in accordance with the increase in cutoff points. The optimal cutoff for determining anticoagulant therapy may be 3 points to minimize nonsurvival with acceptable bleeding complications. The findings of the present study suggested a beneficial association of early intervention with anticoagulant therapy and mortality in the patients with sepsis-induced DIC. Present cutoff points of DIC scoring systems may be suboptimal for determining the start of anticoagulant therapy and delay its initiation.